Analisis Hubungan Pengetahuan dan Perilaku Mahasiswa Tadris Biologi Terhadap Kesehatan Pencernaan - Fitri Ulfa Masruroh; Naila Uswatun Hasanah; Nadia Salsabila; Umatul Wahidah (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Biology education students are prospective biology teachers who will become role models for students in the learning process at school. As prospective teachers, students are required to have good knowledge and behavior. The purpose of this study was to analyze the relationship between digestive system health knowledge and healthy living behavior in biology education students at IAIN Kudus as a result of studying human anatomy and physiology courses. This research is a quantitative descriptive study using survey methods. The subjects in this study were 28 Biology students at IAIN Kudus who had attended lectures on human physiology. Research data in the form of digestive health knowledge and healthy behavior obtained by questionnaire. Data were analyzed descriptively and statistically using product moment correlation analysis using SPSS. The results showed a correlation coefficient of 0.275. The conclusion of this study is that there is a positive correlation between digestive system health knowledge and behavior. Based on this research, it is expected that biology education students can better understand the digestive system material and can apply it in healthy living behaviors.